Figure 1. Richtersius coronifer. A in Morphological and molecular analyses on Richtersius (Eutardigrada) diversity reveal its new systematic position and lead to the establishment of a new genus and a new family within Macrobiotoidea - Guidetti, Roberto; Rebecchi, Lorena; Bertolani, Roberto; Jonsson, Kjell Ingemar; Kristensen, Reinhardt Møbjerg; Cesari, Michele (Zenodo, 2016)
Figure 1. Richtersius coronifer. A, dorsal cuticle of a newborn with pores (arrows) (population from Sweden). B, cuticular pores of a newborn (arrows) (Sweden). C, cuticular pores of a newborn with irregular margin (arrow) (northern Italy 1). D, cuticular pores of a newborn with regular margin (arrow) (Greenland). E, claws on the second leg in an adult (neotype) (Norway). F, frontal view of the claws on the hind leg with an evident stalk system in an adult (arrow) (Greenland). G, claws on the hind leg in a newborn (Greenland). H, claws on the second leg in an adult (northern Italy 1). I, frontal view of the claws on the first leg with an evident stalk system in an adult (arrow) (Sweden). J, lateral view of the claws on the second leg with an evident stalk system in an adult (arrow) (central Italy). A, B: scanning electron microscopy; C–J: phase contrast. Scale bars: A, C–J = 10 µm, B = 1 µm. : Published as part of Guidetti, Roberto, Rebecchi, Lorena, Bertolani, Roberto, Jonsson, Kjell Ingemar, Kristensen, Reinhardt Møbjerg & Cesari, Michele, 2016, Morphological and molecular analyses on Richtersius (Eutardigrada) diversity reveal its new systematic position and lead to the establishment of a new genus and a new family within Macrobiotoidea, pp. 834-845 in Zoological Journal of the Linnean Society 178 (4) on page 838, DOI: 10.1111/zoj.12428, http://zenodo.org/record/5369103